Evaluation of therapeutic efficacy of baloxavir marboxil against high pathogenicity avian influenza virus infection in duck model - Yo Shimazu; Norikazu Isoda; Takahiro Hiono; Yik Lim Hew; Daiki Kobayashi; Misato Shibazaki; Bao Linh Nguyen; Tatsuru Morita; Ryo Daniel Obara; Mariko Miki; Hiromi Osaki; Takao Shishido; et al. (PLoS ONE, 2026)
High pathogenicity avian influenza virus (HPAIV) infections have been frequently reported in wild birds since 2020. Because HPAIV infection has occasionally caused outbreaks in captive rare birds, treatment using antiviral drugs has been considered from the perspective of conservation medicine. In this study, the therapeutic efficacy of baloxavir marboxil (BXM) was evaluated using a duck model to support the establishment of post-infection strategies for captive avian species. Sixteen four-week-old ducks were divided into four groups and intranasally inoculated with the HPAIV strain, A/crow/Hokkaido/0103B065/2022 (H5N1). BXM was administered orally once daily at doses of 12.5, 2.5, 0.5, or 0 mg/kg to each of the four groups from 2 to 6 days post-infection. Blood samples were collected at 2, 8, and 24 hours after the initial BXM administration to measure the plasma concentrations of its active form, baloxavir acid (BXA). All ducks were monitored until 14 days post-infection, and oral and cloacal swabs were collected for virus recovery. All eight ducks administered either 12.5 or 2.5 mg/kg of BXM survived, demonstrating a significant reduction in virus recovery compared with the 0 mg/kg group. To further characterize the relationship between BXA exposure and virus shedding, an additional experiment was conducted in which ducks received a single oral administration of BXM at doses of 7.3, 4.3, or 0.5 mg/kg at 2 days post-infection. Pharmacokinetic/pharmacodynamic analysis of BXA across all dose groups showed that reductions in virus shedding from oral swabs were positively correlated with BXA exposure, and AUC 0–24hr exhibited the strongest association. These findings demonstrate that BXM administration within 48 hours post-HPAIV infection in ducks effectively reduces mortality and virus shedding. Comparison of pharmacokinetic parameters may facilitate the estimation of optimal BXM dosing options for captive avian species.